2023
DOI: 10.1007/s00122-023-04268-3
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the genetic basis of resistance to soybean cyst nematode combining IBD and association mapping

Abstract: Key message IBD analysis clarified the dynamics of chromosomal recombination during the ZP pedigree breeding process and identified ten genomic regions resistant to SCN race3 combining association mapping. Abstract Soybean cyst nematode (SCN, Heterodera glycines Ichinohe) is one of the most devastating pathogens for soybean production worldwide. The cultivar Zhongpin03-5373 (ZP), derived from SCN-resistant progenitor parents, Peking, PI 437654 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…New sources of resistance to cyst nematodes can be discovered through both classical and reverse genetic screening methods. Forward screening techniques, such as Genome-Wide Association Studies (GWAS) and Quantitative Trait Loci (QTL) analysis, are potent tools for identifying genes that confer resistance to pathogens [7][8][9] . The effectiveness of GWAS and QTL analysis is heavily dependent on the precision of infection measurements 10 .…”
Section: Introductionmentioning
confidence: 99%
“…New sources of resistance to cyst nematodes can be discovered through both classical and reverse genetic screening methods. Forward screening techniques, such as Genome-Wide Association Studies (GWAS) and Quantitative Trait Loci (QTL) analysis, are potent tools for identifying genes that confer resistance to pathogens [7][8][9] . The effectiveness of GWAS and QTL analysis is heavily dependent on the precision of infection measurements 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies (GWASs) are an efficient complementary approach to QTL mapping, which allow the determination of marker–trait associations in genetically unstructured accession panels ( Zhu et al., 2008 ). In soybeans, GWASs have been successfully employed to validate Rhg1 and Rhg4 SCN resistance loci ( Han et al., 2015 ; Vuong et al., 2015 ; Tran et al., 2019 ; Tian et al., 2023 ). Further, quantitative trait nucleotides (QTNs) on chromosomes 18 and 19 have been identified in Glycine soja accessions for resistance to HG 2.5.7 (Race 5) using a GWAS ( Zhang et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Investigations into resistance for HG 0 (Race 3) using a GWAS have identified QTNs on chromosomes 7 and 10 ( Tran et al., 2019 ). A recent study using a GWAS identified Rhg1 , Rhg2 , GmNSF RAN07 , and a QTN on chromosome 7 for resistance to HG 0 ( Tian et al., 2023 ). These studies demonstrate the effectiveness of GWASs in identifying marker–trait associations for complex traits such as SCN resistance.…”
Section: Introductionmentioning
confidence: 99%